PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ARTIKULASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VII SMPN 3 PADANG - Rahma Yusra; Zuwirna Wz (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This study discussed about the cooperative learning model in types of articulation towards second grade student’s learning outcomes in social subject at SMPN 3 padang. This study used quantitative method with quasy form. The sample of this research was the second grade student’s in VII2 and VII4 class. The result showed that the average score of students who used cooperative learning model types of articulation was 78,92. It was higher than average score optained by control class which was 73,83. Meanwhile, the calculation of the t-test was optained tcount >ttabel, which is 2,221>2,000 at a significance level of α 0,05, thus tcount>ttable. Therefore, the application of cooperative learning model in types of articulation has significant influence towards the second grade student’s learning outcomes in social subject at SMPN 3 Padang.